Quantum correlation enhanced super-resolution localization microscopy enabled by a fibre bundle camera - Yonatan Israel (Nature Portfolio, 2017)
Classical physics enabled subdiffraction-limited imaging has rarely been extended to the quantum regime. Here, Israelet al. develop a super-resolution localization microscopy based on non-classical photon statistics, enabling optical tracking of multiple quantum emitters.